Effect Of Gross Profit Margin, Return On Assets And Current Ratio On Profit Growth In Property And Real Estate Subsector Companies Listed On The Indonesia Stock Exchange For The Period 2016-2020 - Stevanie Stevanie; Fidellis Wato Tholok (EMaBi: Ekonomi Dan Manajemen Bisnis, 2022)
The object used in this study is a property and real estate subsector company that has gone public in the period 2016-2020. The purpose of the study is to test, explain and empirically prove the influence of Gross Profit Margin, Return On Assets and Current Ratio on profit growth. The method used is a quantitative method using secondary data. The population used is the entirety of the research object. Sample selection using non-probability sampling techniques with purposive sampling methods, so that six property and real estate subsector companies have gone public according to the predetermined time span to be used as samples. The data analysis techniques in this study are descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis test with the help of SPSS (Statistical Program for Social Science) program version 24. The results of this study state that simultaneously there is an influence between Gross Profit Margin, Return On Assets and Current Ratio on profit growth with a significant value of 0.009 < 0.05, while individually states that among the three independent variables there are two variables that have a significant positive influence on profit growth, namely ROA with a sig value. 0.002 < 0.05 and CR with a sig. 0.031 < 0.05. A variable of GPM produces a sig. 0.145 < 0.05, this showing that GPM has a negative effect on profit growth.